Distortion analysis and compensation trials in powder bed fusion 3D metal printing - Mahadhir Ahmad (Nanyang Technological University, 2021)
Thermal stress causes spatial distortions of additively manufactured components using powder bed fusion processes. A compensation of CAD models should be done to mitigate thermal stress induced distortions. The current research focused on the distortion compensation of Inconel 625 parts. To compensate for the printed parts CAD design, finite element analysis was used. Distortion compensation is a method used to get the desired shape as close as the original parts by changing the geometry of the parts to compensate the distortion. A total of twelve pieces were made from Inconel 625 superalloys, four of which were based on the original model and another eight of which were based on the compensation versions. There were 4 different support to compare the distortion. Based on post-manufacturing 3D scans, only a few survived the print and a further analysis was performed to find out why the prints failed. This report uses software such as Magics and Simufact to carry out the experiment. This research also includes the finding of the accuracy differences between the distortion of simulation and the real printing of the parts.